Espectroscopia eletrônica de moléculas halogenadas - Silva, Adevânia Justino da (Universidade Federal de São Carlos, 2022)
We present a theoretical-experimental investigation of the valence state excitation of dichloromethane (CH2Cl2) and trichloromethane (CHCl3) molecules in the gas phase. The CH2Cl2 molecule was investigated using electron energy loss spectroscopy with incident beams of 100 eV. The photoabsorption spectrum (optical oscillator strength) was generated in the energy range from 5 to 21 eV by applying the Bethe-Born condition. Despite the low energy of the incident beam, essentially outside the validity regime of the first Born approximation, on which the Bethe-Born condition is based, and the low energy resolution obtained, the results are in excellent agreement with previous experimental high-resolution data reported in the 5.8–10.8 eV energy range. As far as we are aware, results above 11 eV are unprecedented. Theoretically, the processes of direct ionization of CH2Cl2 and trichloromethane CHCl3 molecules were investigated using the ePolyScat-E3 computational package. Ionization cross-section data and asymmetry parameters for the ionization of the outermost orbitals of these molecules were obtained from the ionization threshold up to 40 eV. Specifically, the ionizations of the 7b2, 3b1, 9a1, 2a2, and 6b2 orbitals for the CH2Cl2, and the 2a2, 9e, 9a1, 8e, 7e, 8a1, and 7a1 for the CHCl3 molecule, were investigated. Theoretical results indicate the contribution of various resonances to the ionization process. However, there are no previous results in the literature for comparison, and a future experimental investigation is necessary to allow validation and a detailed discussion of the theoretical data.
Eletronic spectroscopy of halogenated molecules
Keywords: Seção de choque; Espectroscopia eletrônica; Moléculas halogenadas; Diclorometano; Clorofórmio; Cross section; Halogenated molecules; Dichloromethane; Chloroform; Electronic spectroscopy; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA